Comparison of green and low-carbon development path between Yellow River Basin and Yangtze River Economic Belt--configuration analysis based on “two mountains theory” - Jin, Baoqin; Cui, Jintao; Jia, Haolei; Jiang, Tianfeng (Frontiers in Environmental Science, 2025)
The integration of industrial ecology and ecological industrialization represents a critical mechanism for resolving the economy-ecology dichotomy in riverine systems, exemplifying the paradigm that “ecological assets translate to economic value.” This investigation employs fuzzy-set Qualitative Comparative Analysis (fsQCA) to examine datasets from 18 provincial jurisdictions within the Yellow River Basin and Yangtze River Economic Belt, deconstructing the multifaceted determinants of sustainable development in these watersheds. Results demonstrate that industrial ecology and ecological industrialization exhibit “asymmetric complementarity,” highlighting the necessity for multifactorial approaches to sustainable development rather than monofactorial interventions. The analysis further elucidates distinct developmental trajectories between watersheds: the Yellow River Basin manifests “industrial ecological compensation-driven” and “dual coupling upgrading” pathways, whereas the Yangtze River Economic Belt demonstrates “technological innovation breakthrough” and “system synergy symbiosis” modalities. Eco-industrialization emerges as a fundamental component in high-performance configurations across these watersheds, emphasizing the importance of ecological value transformation at various spatial scales. Through establishing an integrated “theory-method-evidence” framework, this study enhances the explanatory power of the “two-mountain theory” and provides theoretical underpinnings for evidence-based policy formulation in watershed management, offering strategic guidance for implementing contemporary ecological economic systems.